Efektivitas Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Terhadap Hasil Belajar Siswa Kelas XI SMA PGRI Waingapu: Penelitian - Agnes Rambu B. Loti; Iona Lisa Ndakularak (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to evaluate the effectiveness of the Numbered Head Together (NHT) learning model on the mathematics learning outcomes of grade XI students in the topic of function composition at SMA PGRI Waingapu. This research employed a quantitative approach using an experimental method with a One Group Pretest-Posttest Design. The research sample consisted of 33 randomly selected students from class XI-3. The research instrument included pretest and posttest question as well as a student response questionnaire. Data were analyzed using both descriptive and inferential statistics through a one sample t-test. The pretest result showed a mean score of 31,79 with a standard deviation of 11,826, while the posttest result increased to a mean of 83,73 with a standard deviation of 7,027. A total of 85% of students achieved mastery learning after being taught using the NHT model. The t-test showed a significance value of 0,001 (p<0,05), indicating a statistically significant difference between the posttest mean and the Minimum Mastery Criterion. Furthermore, the proportion test showed a significance value of 0,041, supporting the success of the model in improving student mastery. Student responses to the NHT model were also categorized as positive, with 70% agreement on most aspects. Based on these findings, it is concluded that the NHT model is effective in improving students mathematics learning outcomes.